Crowdfunding Untuk Membangun Usaha Yang Berkualitas - Dayina Patna; I Putu Agus Swastika (Primakara University, 2019)
Media information has a very big role in conveying information to the public. This is also supported by the development of information technology that can be used according to the needs of the user. In building a business we must be able to follow the development of today's business science. One of them is in obtaining funds or obtaining capital to support the business that is being built. Media information that is widely used to support this is the website. Many entrepreneurs use banking services to seek venture capital. However, now entrepreneurs have started using modern ways to get capital, namely Crowdfounding Sites which are an alternative for entrepreneurs to find funds to start their own business. From this site, businesses expand their business by obtaining venture capital. In Indonesia, crowdfunding sites have started to emerge, such as kitabisa.com,Jadikan.com, Ayopeduli.com, usahaan.net, gagas.web.id, bursaside.com and tedung.com. With this site, entrepreneurs can change their views on how to obtain initial capital for the businesses they run. With this crowdfounding site, it is hoped that entrepreneurs will be able to build a quality business and be able to keep abreast of developments in the information technology-based business world.